Ethnic Cleansing of Rohingyas in Myanmar: An Examination of Security Concerns for India - Ahmad Khan, Samim; Mohi-Ud-Din Badana, Tahir (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the situation in Myanmar's Rakhine state, focusing on the Rohingya ethnic community. It explores Myanmar's policies towards the Rohingya since its establishment, considering the involvement of key actors like political parties and the military. The argument presented is that the government is systematically weakening and expelling the Rohingya, leading to ethnic cleansing. The ethnic cleansing of the Rohingya in Myanmar has implications for national security in India. The Indian government has portrayed the Rohingya as "illegal" and a threat to national security, leading to their exclusion from the Citizenship (Amendment) Act 2019. However, the persecution of the Rohingya is not solely based on ethnic and religious tensions but is also influenced by the nation-building process in Myanmar, which has excluded and marginalized the Rohingya population. The military regime in Myanmar, along with other security forces, has played a significant role in perpetrating crimes against the Rohingya. Additionally, the conflict in Rakhine, where the Rohingya reside, has geo-strategic and economic dimensions, with China and India having vested interests in the region. Therefore, the ethnic cleansing of the Rohingya poses both humanitarian and security challenges for India. The primary goal of the paper is to gain a deep understanding of the issue, given its significance as a major cause of the growing number of Rohingya refugees. The research aims to contribute to policy recommendations and formulations for addressing and resolving this longstanding conflict.